Item Difficulty of Fugl-Meyer Assessment for Upper Extremity in Persons With Chronic Stroke With Moderate-to-Severe Upper Limb Impairment - Hijikata, Nanako; Kawakami, Michiyuki; Ishii, Ryota; Tsuzuki, Keita; Nakamura, Takuya; Okuyama, Kohei; Liu, Meigen (Frontiers in Neurology, 2020)
Background and Purpose: Limited research has been conducted with the aim of understanding which upper extremity movements are difficult for persons with severe chronic stroke. The purpose of this study was to test the structure of the Fugl-Meyer Assessment for Upper Extremity (FMA-UE) using Rasch analysis in persons with chronic stroke with moderate to severe deficits and to determine the item difficulty hierarchy. Methods: This was a secondary analysis of data from previous randomized, controlled trials or clinical trials. The participants were 101 persons with chronic stroke with moderate to severe hemiparesis (time after onset of stroke, 1375.3±1157.9 days; the 33-item FMA-UE, 31.1±12.8). Principal component analysis and infit statistics were used to evaluate dimensionality. Rasch analysis using a rating scale model was performed, and item difficulty was determined. Results: Six misfit items were removed. The results showed that the 27-item FMA-UE was unidimensional. Rasch analysis showed that the movements performed within synergies were among the easiest items. Shoulder and elbow movements were among the easiest items, whereas forearm and wrist movements were among the moderately to most difficult items. Hand items spanned various difficulty levels. Discussion and Conclusions: The FMA-UE is a valid assessment tool of upper extremity motor function in persons with chronic stroke with moderate to severe deficits. The results showed that item difficulty was consistent with the stepwise recovery course proposed by Fugl-Meyer. The movements that are difficult for patients with moderate to severe chronic paresis were determined, which would enable comparison of each movement using a measure of motion difficulty in future studies.